The Role of ABCB1, ABCG2, and SLC Transporters in Pharmacokinetic Parameters of Selected Drugs and Their Involvement in Drug–Drug Interactions - Kajetan Kiełbowski; Małgorzata Król; Estera Bakinowska; Andrzej Pawlik (Membranes, 2024)
Membrane transporters are expressed in a wide range of tissues in the human organism. These proteins regulate the penetration of various substances such as simple ions, xenobiotics, and an extensive number of therapeutics. ABC and SLC drug transporters play a crucial role in drug absorption, distribution, and elimination. Recent decades have shown their contribution to the systemic exposure and tissue penetration of numerous drugs, thereby having an impact on pharmacokinetic and pharmacodynamic parameters. Importantly, the activity and expression of these transporters depend on numerous conditions, including intestinal microbiome profiles or health conditions. Moreover, the combined intake of other drugs or natural agents further affects the functionality of these proteins. In this review, we will discuss the involvement of ABC and SLC transporters in drug disposition. Moreover, we will present current evidence of the potential role of drug transporters as therapeutic targets.